2015
DOI: 10.1016/j.rmed.2015.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to gun violence and asthma among children in Puerto Rico

Abstract: Background and Objectives Although community violence may influence asthma morbidity by increasing stress, no study has assessed exposure to gun violence and childhood asthma. We examined whether exposure to gun violence is associated with asthma in children, particularly in those reporting fear of leaving their home. Methods Case-control study of 466 children aged 9 to 14 years with (n=234) and without (n=232) asthma in San Juan, Puerto Rico. Lifetime exposure to gun violence was defined as hearing a gunsho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 30 publications
4
33
0
Order By: Relevance
“…7,35 Because of sample size and statistical power, the analysis of African ancestry and asthma or total IgE was first conducted for the combined cohort and then conducted separately for each study site. 38 maternal history of asthma, 39 early-life exposure (in utero or before 2 years of age) to environmental tobacco smoke (ETS), 40 exposure to gun violence, 21 and (for the analysis of the combined cohort) study site. 3 The model for total IgE was further adjusted for case-control status.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…7,35 Because of sample size and statistical power, the analysis of African ancestry and asthma or total IgE was first conducted for the combined cohort and then conducted separately for each study site. 38 maternal history of asthma, 39 early-life exposure (in utero or before 2 years of age) to environmental tobacco smoke (ETS), 40 exposure to gun violence, 21 and (for the analysis of the combined cohort) study site. 3 The model for total IgE was further adjusted for case-control status.…”
Section: Discussionmentioning
confidence: 99%
“…17,[19][20][21][22][23] In a prior study of 1,213 Puerto Rican children, we reported that a history of child abuse was associated with 2.5 times increased odds of asthma (95% CI, 1.27-5.00; P ¼ .009). 20 These findings were later replicated in a large longitudinal cohort of adult African American women.…”
Section: Not Exposed To Gun Violencementioning
confidence: 92%
See 3 more Smart Citations